Forge a poetic form: Estancias by Javier Sologuren - Guizado Yampi, Renato (2016)
This article attempts to study the Estancia by Javier Sologuren, as an accurately poetic form which contains a cluster of features shared by all the poems in this collection. In order to do so, we outline a descriptive definition that allows us to recognize a poetic form in the Estancia, along with a structural innovation,  identifying stylistic patterns, which would serve as differential elements from objective demonstrations, in a comparative context.